Orientation‐dependent electrical property and domain configuration of Mn‐doped Pb(In0.5Nb0.5)O3–PbTiO3 single crystal. Issue 1 (10th September 2018) - Qiao, Huimin; He, Chao; Wang, Zujian; Li, Xiuzhi; Liu, Ying; Tailor, Hamel; Long, Xifa
Abstract: Orientation dependence of electrical properties and domain configurations of 8 mol% Mn‐doped rhombohedral PIN‐PT (0.68Pb(In0.5 Nb0.5 )O3 –0.32Pb(Ti0.92 Mn0.08 )O3 ) rhombohedral single crystals were investigated with an emphasis on studying the variations of coercive field ( E C ), internal field ( E i ) on domain patterns. Our results showed that for both [001] and [110]‐oriented samples, the coercive field and internal field decreased with temperature ( T ) increasing in rhombohedral phase, and a peak appeared above rhombohedral‐tetragonal phase transition temperature ( T RT ). The abnormal peaks between T RT and Curie temperature on E C ‐ T and E i ‐ T plots are explained by taking into consideration the ferroelectric phase transition and variation of defect polarization, which provides assistant comprehension on the dynamic of defect dipoles during phase transition at high temperature. Bubble‐ and ribbon‐like domain patterns were observed in (001)‐ and (110)‐plane, respectively, and smaller value of short‐length correlation radius in (001)‐ plane indicates less aggregation of polar nanoregions in this crystallographic plane than that in (110)‐plane.